Ethnographic constructions of Indigenous others - Byrne, George (Researcher), author.
1 online resource (xii, 229 pages)
Keywords: "This book examines the ways in which indigeneity interacts with climate change politics at multiple levels, and at the same time offers a self-critical reflection on the role of ethnographic research (and researchers) in this process. Through a multi-sited ethnography, it shows how indigeneity and climate change mitigation are at this point so intensely intertwined that one cannot be clearly understood without considering the other. While indigenous identities have been (re)defined in relation to climate change, it argues that indigenous peoples continue to subvert pervasive notions of the nature/culture dichotomy and disrupt our understanding of what it means to be human in relation to nature. It encourages students and researchers in anthropology, international development, and other related fields to engage in more meaningful reflection on the epistemic shortcomings of 'the West', including in our own research, and to acknowledge the ongoing role of power, coloniality, extractivism, and Whiteness in Climate Change discourses"--